2023
DOI: 10.1021/acsami.2c19240
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Friction across the First-Order Charge Density Wave Phase Transition of 1T-TaS2

Abstract: Nanotribology using atomic force microscopy (AFM) can be considered as a unique approach to analyze phase transition materials by localized mechanical interaction. In this work, we investigate friction on the lamellar transition metal dichalcogenide 1T-TaS2, which can undergo first-order charge density wave (CDW) phase transitions. Based on temperature-dependent atomic force microscopy under ultrahigh vacuum conditions (UHV), we can characterize the general friction levels across the first-order phase transiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In this study, we report that the mesoscopic phase transformation can be observed and visualized by friction force microscopy (FFM), an extended technique of static-mode AFM. The FFM detects the torsional response of the AFM cantilever on the sample surface and measures the friction properties of the sample. As friction properties have been utilized for characterizing phase behaviors in many cases of organic and inorganic materials, FFM has the potential for evaluating the crystalline states of OSC films. It is found in the FFM images of spin-coated films of 2-C8-BTNT that high-friction and low-friction phases are separately formed at a mesoscopic scale during annealing processes.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we report that the mesoscopic phase transformation can be observed and visualized by friction force microscopy (FFM), an extended technique of static-mode AFM. The FFM detects the torsional response of the AFM cantilever on the sample surface and measures the friction properties of the sample. As friction properties have been utilized for characterizing phase behaviors in many cases of organic and inorganic materials, FFM has the potential for evaluating the crystalline states of OSC films. It is found in the FFM images of spin-coated films of 2-C8-BTNT that high-friction and low-friction phases are separately formed at a mesoscopic scale during annealing processes.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in the field of tribology in the past years have primarily focused on the graphene's frictional properties on the basal plane and across step edges, which have revealed numerous interesting phenomena such as the dependence of friction on factors like thickness, crystalline orientation, sliding direction, and binding strength to the substrate, etc. [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] Especially, the intrinsic weak interlayer van der Waals interaction and low out‐of‐plane bending rigidity of 2D materials result in a lifting of the top layer in front of the scanning tip, that is, the puckering effect, [ 11 , 15 , 22 ] leading to friction increasing with decreasing sample thickness. [ 11 , 15 , 23 ] Moreover, the contact quality between the top layer and the scanning tip evolves with scanning time, with friction force gradually increasing for a few initial atomic periods before reaching a constant value.…”
Section: Introductionmentioning
confidence: 99%